HUBUNGAN PERSONAL HIGIENE DAN PEMAKAIAN ALAT PELINDUNG DIRI TERKAIT TERJADINYA PENYAKIT KULIT PADA SUPIR PENGANGKUT SAMPAH : (STUDI LITERATUR) - Wirdatun Hasanah; Susilawati Susilawati (CV. ADIBA ADISHA AMIRA, 2023)
Personal Hygiene is a way of human self-care to maintain health both physically and psychologically. Maintenance of personal hygiene greatly determines health status, where consciously and on personal initiative in maintaining health and preventing the occurrence of a disease. Personal hygiene greatly affects health, especially for garbage transporters. Trash transport drivers are basically workers who really need to pay attention to hygiene in their daily lives. Garbage collection drivers are very susceptible to skin diseases if they do not use proper personal protective equipment (PPE) and hygiene while doing their job. Method: Using literature studies from national journals by summarizing the topics in the articles. Objective: To determine the effect of personal hygiene on the health problems of garbage truck drivers. The results of the study using a literature review found that there was a relationship between personal hygiene and personal protective equipment with skin diseases experienced by garbage transport drivers.